Expression of tuberculosis antigen ESAT-6 in Nicotiana tabacum using a potato virus X-based vector - Zelada, Alicia Mercedes (2006)
A good candidate antigen to create a therapeutic vaccine against TB is the ESAT-6 protein. Antigens produced in plants have already been successfully used as experimental vaccines, and small single-stranded RNA plant viruses have emerged as promising tools to rapidly express large amounts of foreign proteins in susceptible host plants. Here, we present the expression of ESAT-6 protein in Nicotiana tabacum using a vector based on potato virus X (PVX). The complete ESAT-6 open reading frame is expressed as a fusion protein with the 2A peptide of Foot and Mouth Disease Virus and the amino terminal of the PVX coat protein (CP) (PVXESAT-6). This strategy allows the production of free CP and ESAT-6 as well as fused ESAT-2A-CP to obtain recombinant chimaeric virions expressing ESAT-6 at the surface to be used as particulate antigen in vaccination. ESAT-6 expression was tested in agroinfiltrated tobacco leaves and products of the expected molecular masses corresponding to cleaved CP and ESAT-2A-CP fusion protein were observed, with ESAT-6 yields ranging from 0.5% to 1% of total soluble protein. Our study describes for the first time the expression of the ESAT-6 protein in tobacco plants using a PVX-derived vector. This strategy should serve as a convenient, rapid, low-cost expression system and can also be used for the assessment of ESAT-6 production and function prior to stable plant transformation.